2011
DOI: 10.1111/j.1537-2995.2011.03386.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting overall viability of cord blood harvests

Abstract: This study identifies optimal TTF for different collection volumes to maintain WBC viability of the collected CB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Several studies have shown that the functionality of CD34+ cells can be reduced significantly after cryopreservation . In one of these studies, annexin V–negative CD34+ cells correlated with NOD/SCID mouse hematopoietic repopulating ability, indicating as would be expected that apoptotic CD34+ cells fail to engraft . Our results have extended these studies by showing a significant reduction in UCB CD34+ cell viability with both the 7‐AAD and annexin V methods used after cryopreservation that is associated with time to cryopreservation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Several studies have shown that the functionality of CD34+ cells can be reduced significantly after cryopreservation . In one of these studies, annexin V–negative CD34+ cells correlated with NOD/SCID mouse hematopoietic repopulating ability, indicating as would be expected that apoptotic CD34+ cells fail to engraft . Our results have extended these studies by showing a significant reduction in UCB CD34+ cell viability with both the 7‐AAD and annexin V methods used after cryopreservation that is associated with time to cryopreservation.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies have shown that the functionality of CD34+ cells can be reduced significantly after cryopreservation . In one of these studies, annexin V–negative CD34+ cells correlated with NOD/SCID mouse hematopoietic repopulating ability, indicating as would be expected that apoptotic CD34+ cells fail to engraft .…”
Section: Discussionmentioning
confidence: 98%
“…However, in this study, we found small but significant losses of CFUs, CD34+ cells, and TNCC that occur in CB processed at least 24 hours after delivery compared to those processed less than 10 hours from collection. Our findings are similar to those of Pope and colleagues who recently correlated decreasing viability with increased time from collection to freeze. These findings indicate that delays in processing could impact the yield of bankable CBUs.…”
Section: Discussionmentioning
confidence: 99%
“…Our conclusion is contradictory to the results of some authors who showed that the broad range of anticoagulant concentration did not affect cell viability, though a gradual loss of cell viability was observed after storage for 25-48 h and particular after 49-80 h [13]. But there are authors that suggest that the ratio of anticoagulant could determine low cell viability for the units with the collected UCB volume of less than 60 ml, even if the amount of anticoagulant in collection bags was lower (29 ml) [29].…”
Section: Tablementioning
confidence: 85%
“…To date, we identified only one study that indicated the collected UCB volume as a significant factor affecting the pre freeze cell viability and showed the combined effects of collected blood volume and time from collection to freezing on cell viability [29].…”
Section: Tablementioning
confidence: 99%